Charles Williams as a Shakespearean critic in the age of modernism - Cotterill, Rowland (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Charles Williams, known as novelist, poet, and member of the inter-war "Inklings" circle of writers, also contributed to Modernist critical debate, particularly in his writings on Shakespeare. He responded distinctively to contemporary critical emphases on "Elizabethan theatrical convention" and aesthetic and poetic autonomy.
Keywords: poetry; divisions; change; solitude; action